Proyecto de factibilidad para la creación de un centro de masajes y rehabilitación en la ciudad de Macará, provincia de Loja - Salas Jiménez, Nilda Cecilia (2015)
The proposed project is located in a local context, specifically in the city of Macara Macara Canton province of Loja, led to the economically active population. The main objective of this work is to determine the feasibility of creating a Massage and Rehabilitation Center in the city of Macara that meets personalized to people that need it, with highly trained professionals. It will provide a high quality service, drawing on the expertise of its employees, also have the complement of special teams use the latest technology and quality raw materials. 62% of the economically active population accepts the creation of this center Massage and Rehabilitation, use annual per capita will be 48 sessions of one hour each, generating an unmet demand for 180,918 sessions for the first year of life . The size of the center is 9,462 clients attending a massage and rehabilitation with a duration of one hour, with the focus on two shifts effective for 6 hours with 5 employees, allowing one looks 5, 23% of the market. The Center is located in the Barrio Amazon in the streets Carlos Veintemilla and Loja, whose owner will leased for 5 years. The Center will create legal and legally as Sole Limited Liability Company. Fulfilling social responsibility to create jobs, 5 seats in the operational area for Medical Traumatology, 2 Physiotherapists, 2 Masseurs, 1 Psicorehabilitadora be created; in the administrative area 3 posts for one manager, one secretary and one will be generated Concierge also be contracted professional services having no connection to a meter and a lawyer, the latter when required. The investment required to operate this center will be $ 44,261.58, the same to be invested in fixed assets the amount of 24,464.16; Deferred Assets $ 7,680 and Working Capital $ 12,117.42 for one month. The 53.84% of the investment will be financed by the owner and 46.16% by Banco de Fomento to an annual interest rate of 11% with semiannual payments for a period of four years. The costs indicate that for the first year will be $ 142,465.42, which set a unit cost of $ 15.06 per session (time) to determine the sale price a profit of 6.27 was established in year % meaning that the sale price for a massage and rehabilitation will be $ 16. Revenues for the first year of the Centre shall 151,392, generating a profit for the owner of $ 5,121.63. The breakeven points that must sell $ 125,598.23 and work with 82.96% in the first year in order to avoid losses. Cash flow notes that the first year there will be a liquidity of $ 5,963.18 for the owner. The financial evaluation indicators are all positive for the Center since the NPV is $ 27,476.22, the IRR is 27.26%, the benefit cost ratio indicates that for every dollar invested 17 cents of profit will be gained, the recovery period will be 4 years 1 month and 2 days. The sensitivity analysis showed that income can be reduced up to 4.25% and increase costs 4.93%. I conclude by stating that conclusions of all work which synthesizes all objectives could be met, and recommendations to schools and investors were established